Altruistic Suicide Committed by Terrorist - Cyrena Temaluru; Adrianus Eliasta Meliala (Universitas Budi Luhur, 2026)
Altruistic suicide is a term introduced by Durkheim in his monograph Suicide, which emphasizes the high level of integration between the actor of suicide and his/her social group. Meanwhile, if we look at the altruistic concept, it is the highest self-actualization concept of an adult by being useful to other people, which this concept becomes a golden moral in some cultures and dogma. These concepts conflict when we put them into the terrorism concept, which already took victims other than the perpetrators himself/herself, not only combatants but also civilians. This study aims to determine whether suicide committed by a terrorist is altruistic suicide from a criminological point of view. This study used a qualitative method by conducting semi-structured interviews with academic and practitioner observers and conducting a literature study of suicide cases by terrorists in Indonesia. As a result, it was found that altruistic suicide in terrorism was specific altruistic, which is a product of social construction in terrorist groups, where they produce a high level of integration that encourages someone to sacrifice his or her life for the benefit of his or her group and destruction for other groups.